Death-associated protein kinase increases glycolytic rate through binding and activation of pyruvate kinase - Mor, I.; Carlessi, Rodrigo; Ast, T.; Feinstein, E.; Kimchi, A. (2012)
Death-associated protein kinase (DAPk), a multi-domain serine/threonine kinase, regulates numerous cell death mechanisms and harbors tumor suppressor functions. In this study, we report that DAPk directly binds and functionally activates pyruvate kinase M2 (PKM2), a key glycolytic enzyme, which contributes to the regulation of cancer cell metabolism. PKM2 was identified as a novel binding partner of DAPk by a yeast two-hybrid screen. This interaction was validated in vitro by enzyme-linked immunosorbent assay using purified proteins and in vivo by co-immunoprecipitation of the two endogenous proteins from cells. In vitro interaction with full-length DAPk resulted in a significant increase in the activity of PKM2. Conversely, a fragment of DAPk harboring only the functional kinase domain (KD) could neither bind PKM2 in cells nor activate it in vitro. Indeed, DAPk failed to phosphorylate PKM2. Notably, transfection of cells, with a truncated DAPk lacking the KD, elevated endogenous PKM2 activity, suggesting that PKM2 activation by DAPk occurs independently of its kinase activity. DAPk-transfected cells displayed changes in glycolytic activity, as reflected by elevated lactate production, whereas glucose uptake remained unaltered. A mild reduction in cell proliferation was detected as well in these transfected cells. Altogether, this work identifies a new role for DAPk as a metabolic regulator, suggesting the concept of direct interactions between a tumor suppressor and a key glycolytic enzyme to limit cell growth. Moreover, the work documents a unique function of DAPk that is independent of its catalytic activity and a novel mechanism to activate PKM2 by protein-protein interaction. © 2012 Macmillan Publishers Limited All rights reserved.